Settlement of the Malamoi Community Customary Land Dispute in Sorong Regency: A Review of Legal and Social Aspects - Benhur Raubert Putirulan; Kristi Warista Simanjuntak; Paul Przemysław Polański (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
The resolution of land disputes in Sorong Regency, West Papua, highlights the complexity of issues involving the Malamoi indigenous community and other parties. This research uses an empirical approach to understand the dispute resolution process and the obstacles faced. The results showed that the settlement was conducted through out-of-court peaceful channels, known as Alternative Dispute Resolution (ADR), such as mediation and deliberation. Although court institutions exist, the ADR approach is more in line with the values and needs of indigenous peoples, who tend to prioritize harmonization and quick resolution. However, there are internal and external barriers, such as emotional temperament and third-party interference, which affect the resolution process. Overcoming these obstacles requires awareness of the importance of deliberation in dispute resolution, as well as the active role of all parties. Land dispute resolution in Sorong Regency requires an inclusive and adaptive approach, combining formal institutions and alternative methods to achieve broader justice for all parties involved.